Inhibition of Polyamine Oxidase Prevented Cyclin-Dependent Kinase Inhibitor-Induced Apoptosis in HCT 116 Colon Carcinoma Cells - Çoker Gürkan, Ajda; Palavan Ünsal, Narçin; ARISAN, ELİF DAMLA; YERLİKAYA, PINAR OBAKAN (Springer, Van Godewijckstraat 30, 3311 Gz Dordrecht, Netherlands, 2013)
Roscovitine and purvalanol are novel cyclin-dependent kinase (CDK) inhibitors that prevent cell proliferation and induce apoptotic cell death in various cancer cell lines. Although a number of studies have demonstrated the potential apoptotic role of roscovitine, there is limited data about the therapeutic efficiency of purvalanol on cancer cells. The natural polyamines (PAs) putrescine, spermidine, and spermine have essential roles in the regulation of cell differentiation, growth, and proliferation, and increased levels of these compounds have been associated with cancer progression. Recently, depletion of intracellular PA levels because of modulation of PA catabolic enzymes was shown to be an indicator of the efficacy of chemotherapeutic agents. In this study, our aim was to investigate the potential role of PA catabolic enzymes in CDK inhibitor-induced apoptosis in HCT 116 colon carcinoma cells. Exposure of cells to roscovitine or purvalanol decreased cell viability in a dose- and time-dependent manner. The selected concentrations of roscovitine and purvalanol inhibited cell viability by 50 % compared with control cells and induced apoptosis by activating the mitochondria-mediated pathway in a caspase-dependent manner. However, the apoptotic effect of purvalanol was stronger than that of roscovitine in HCT 116 cells. In addition, we found that CDK inhibitors decreased PA levels and significantly upregulated expression of key PA catabolic enzymes such as polyamine oxidase (PAO) and spermine oxidase (SMO). MDL-72,527, a specific inhibitor of PAO and SMO, decreased apoptotic potential of CDK inhibitors on HCT 116 cells. Moreover, transient silencing of PAO was also reduced prevented CDK inhibitor-induced apoptosis in HCT 116 cells. We conclude that the PA catabolic pathway, especially PAO, is a critical target for understanding the molecular mechanism of CDK inhibitor-induced apoptosis.
Keywords: colon cancer; apoptosis; CDK inhibitors; polyamine catabolism breast-cancer cells; roscovitine-induced apoptosis; chemotherapeutic-agents; prostate-cancer; leukemia-cells; r-roscovitine; in-vivo; metabolism; induction; kolon kanseri; apoptoz; CDK inhibitörleri; poliamin katabolizması; meme kanseri hücreleri; roscovitine bağlı apoptoz; kemoterapötik-maddeler; prostat kanseri; lösemi hücreleri; metabolizma; indüksiyon